A modified AUGIS Delphi process to establish research priorities in bariatric and metabolic surgery. Issue 1 (24th October 2019) - Wilson, Michael S. J.; Knight, Stephen; Vaughan‐Shaw, Peter; Blakemore, Alex I.; O'Kane, Mary; Boyle, Christopher; Small, Peter; Mahawar, Kamal; ,
Summary: Delphi methodology may be utilized to develop consensus opinion among a group of experts. The aim of our study was to use a modified Delphi process to determine the future research priorities among bariatric and metabolic healthcare professionals in the United Kingdom. Members of the Association of Upper Gastrointestinal Surgeons and the British Obesity and Metabolic Surgery Society were invited to submit individual research questions via an online survey (phase I). Two rounds of prioritization by multidisciplinary expert healthcare professionals (phase II and III) were completed to determine a final list of high‐priority research questions. Fifty‐one bariatric and metabolic surgery‐focused questions were identified in phase I. Thirty‐five questions were taken forward for prioritization in phase II. Eleven high‐priority questions were identified in phase III. The final list of high‐priority questions had an emphasis on the pathophysiology and long‐term sequelae of bariatric and metabolic surgery. A modified Delphi process has produced a list of 11 high‐priority research questions in bariatric and metabolic surgery. Future studies and awards from funding bodies should reflect this consensus list of prioritized questions in the interest of improving patient care and encouraging collaborative research across multiple centres.